Wedrink vs. Mixue di Mata Konsumen - Mellisa Zahra Nuraini; Nurifa Aulia Anggraeni; Rasifa Mar Atuzzulfa; Ruth Natalia Susanti (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to analyze consumer behavior towards two ready-to-drink beverage brands, Wedrink and Mixue, in Kudus Regency, as well as the psychological, social, and cultural factors that influence consumer preferences. The method used is descriptive quantitative with 26 respondents aged <18 to >27 years, selected through purposive sampling. Data were collected using a 20-item Likert scale questionnaire and in-depth interviews. The results show that consumer preferences are influenced by the taste of the drink, ease of access, price/promotion, as well as social and social media influence. The consumption of trendy drinks like Wedrink and Mixue not only satisfies physiological needs but also serves as a means of self-reward, relaxation, and social identity affirmation. Consumers tend to choose Mixue due to its ease of access and greater number of outlets, while Wedrink attracts attention with its distinctive flavor variants and unique experience. This study shows that the behavior of young consumers is influenced by a combination of rational, emotional, and symbolic factors, with social media playing a significant role in shaping brand perceptions and preferences. These findings provide insights for producers in designing marketing strategies that consider the social and emotional dimensions of consumers.